2020
DOI: 10.1111/coin.12269
|View full text |Cite
|
Sign up to set email alerts
|

Improved fuzzy weighted‐iterative association rule based ontology postprocessing in data mining for query recommendation applications

Abstract: The usage of association rules is playing a vital role in the field of knowledge data discovery. Numerous rules have to be processed and plot based on the ranges on the schema. The step in this process depends on the user's queries. Previously, several projects have been proposed to reduce work and improve filtration processes. However, they have some limitations in preprocessing time and filtration rate. In this article, an improved fuzzy weighted‐iterative concept is introduced to overcome the limitation bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The performance of the proposed QGMS framework is baselined with other models for query recommendation namely the IWFIAR, 27 PQRA, 26 QRM, 25 QRESSG, 34 RSR, 18 QuantQueryEXP, 28 QRMExpS 20 for a set of two datasets namely the CHiC dataset and the Spring 2006 Query Logs dataset. The reason for choosing an array of baseline strategies is to bring out the importance of semantically driven strategies using ontologies in the context of query recommendation for a successful semantic search.…”
Section: Results and Performance Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The performance of the proposed QGMS framework is baselined with other models for query recommendation namely the IWFIAR, 27 PQRA, 26 QRM, 25 QRESSG, 34 RSR, 18 QuantQueryEXP, 28 QRMExpS 20 for a set of two datasets namely the CHiC dataset and the Spring 2006 Query Logs dataset. The reason for choosing an array of baseline strategies is to bring out the importance of semantically driven strategies using ontologies in the context of query recommendation for a successful semantic search.…”
Section: Results and Performance Evaluationmentioning
confidence: 99%
“…Apart from the genetic algorithm, the strategy intelligently integrates compound probability, Jaccard index for clicks and words separately, and the ratio of length of longest common subsequence to the maximum length of the queries. Sumathi and Akilandeswari 27 have proposed a weighted fuzzy iterative technique with association rules R e t r a c t e d for domain-specific ontologies to recommend queries effectively. Kaushik et al 28 have incorporated a Deutsch-Jozsa algorithm in an altered manner for query recommendation by giving it a computational flavor using quantum principles.…”
Section: Other Alternative Approaches To Query Recommendationmentioning
confidence: 99%
“…To extract the relevant knowledge from the huge datasets, association rule mining (ARM) is classified as a promising technology for data prediction analysis (Ţăranu, 2016; Altaf et al , 2017; Sarno et al , 2020). ARM is one of the commonest and most effective techniques for exploring the recurring relationships in data through frequent pattern mining (Sumathi and Akilandeswari, 2020). The objective of association rule mining is to discover essential knowledge from databases and identify the associations among the items in the datasets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [37], FOs are used to define the necessary semantic for controlling smart homes using the internet of Things. In [38], Sumathi et al propose an ontology that stores information about an information processing technique for query recommendation applications. It can be concluded that FO is a quite recent field that is evolving and changing due to the research made on the area.…”
Section: Fuzzy Ontologiesmentioning
confidence: 99%